2022
DOI: 10.1186/s12874-022-01528-6
|View full text |Cite
|
Sign up to set email alerts
|

The injury severity score: an operations perspective

Abstract: Background The statistical evaluation of aggregation functions for trauma grades, such as the Injury Severity Score (ISS), is largely based on measurements of their Pearson product-moment correlation with mortality. However, correlation analysis makes assumptions about the nature of the involved random variables (cardinality) and their relationship (linearity) that may not be applicable to ordinal scores such as the ISS. Moreover, using correlation as a sole evaluation criterion neglects the dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 20 publications
1
8
1
1
Order By: Relevance
“…The lack of such correlation in our study might be explained by the fact that non-survivors (with higher positive fluid balance), had the CRRT stopped prematurely, before full de-resuscitation, due to death. It should be noted that the ISS in our study is relatively high compared to other studies ( 51 , 52 ); however, this fact can be explained by the specification of the Level 3 Trauma Center in our hospital. The Trauma Center in our hospital is dedicated to a large region of southern Poland, where the most severe trauma victims are transported (mainly by the air transport—helicopters) in situations where very specialist treatment is necessary and when other, less specialist trauma centers in the region cannot handle them.…”
Section: Discussioncontrasting
confidence: 78%
“…The lack of such correlation in our study might be explained by the fact that non-survivors (with higher positive fluid balance), had the CRRT stopped prematurely, before full de-resuscitation, due to death. It should be noted that the ISS in our study is relatively high compared to other studies ( 51 , 52 ); however, this fact can be explained by the specification of the Level 3 Trauma Center in our hospital. The Trauma Center in our hospital is dedicated to a large region of southern Poland, where the most severe trauma victims are transported (mainly by the air transport—helicopters) in situations where very specialist treatment is necessary and when other, less specialist trauma centers in the region cannot handle them.…”
Section: Discussioncontrasting
confidence: 78%
“…Recent advances have been hopeful. A retrospective study on 167 trauma patients showed that when a set of 63 genes were incorporated into the genomic score, they appeared to perform better in predicting outcomes than the Injury Severity Score and the Acute Physiology and Chronic Health Evaluation II (APACHE-II) (VSV1) metric[ 14 - 16 ]. Gene expression analyses have also been successful in distinguishing the molecularly defined subtypes of sepsis and even estimating their responses to various treatment modalities, such as corticosteroid therapy[ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…A prespecified form was used to general data from patients' medical records and outpatient interviews, including the Injury Severity Score (ISS) [ 12 ], associated injuries, surgical interventions and functional outcomes at the follow-up period. Ischemia time was defined as the time interval from trauma to blood flow restoration.…”
Section: Methodsmentioning
confidence: 99%